2020
DOI: 10.1111/jocd.13426
|View full text |Cite
|
Sign up to set email alerts
|

Moist exposed burn therapy in recovery of patients with immature, red hypertrophic scars successfully treated with a pulsed dye laser in combination with a fractional CO2 laser

Abstract: Background The efficacy of pulsed dye laser combined (PDL) and UltraPulse fractional CO2 in treatment of hypertrophic scars is well documented. The present study investigates the efficacy of moist exposed burn ointment (MEBO)/moist exposed burn therapy (MEBT) in postlaser wound management. Methods Sixty‐one patients with immature, red hypertrophic scars were enrolled in this clinical trial. Patients were randomly divided into two groups: (a) the MEBO treatment group (n = 30) and (b) the control group (n = 31) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…Fractional CO2 laser and 595-nm PDL in treating hypertrophic scars build on the principle of selective photothermolysis, and their e cacies have been clinically proved [9][10][11][12][13][14][35][36][37][38][39][40][41][42][43][44][45][46]. In current study, we attempted combined use of the two laser modalities in rabbit models, with BMP-7 and Fas expression detected in the HS tissues.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Fractional CO2 laser and 595-nm PDL in treating hypertrophic scars build on the principle of selective photothermolysis, and their e cacies have been clinically proved [9][10][11][12][13][14][35][36][37][38][39][40][41][42][43][44][45][46]. In current study, we attempted combined use of the two laser modalities in rabbit models, with BMP-7 and Fas expression detected in the HS tissues.…”
Section: Discussionmentioning
confidence: 99%
“…PDL, another laser modality with selective photothermolysis, has been clinically used for decades, and can effectively inhibit microvasculature in HSs [3,9]. Previous studies revealed that PDL can reduce abnormal mast cells, broblasts and keratinocytes in HSs [10][11][12], and particularly could produce better effects by 585-nm wavelength for post-surgery scars, and promote vascularity and pliability of skins at the HSs [9,12,[35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations